2019
DOI: 10.1096/fj.201900499rr
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of UBE2N‐dependent CDK6 protein degradation by miR‐934 promotes human bladder cancer cell growth

Abstract: Because bladder cancer (BC) is one of the most common malignant cancers of the urinary system, identification of BC cell growth‐associated effectors is of great significance. Cyclin‐dependent kinase (CDK)6 is a member of the CDK family of cell cycle‐related proteins and plays an important role in cancer cell growth. This is borne out by the fact that a CDK6 inhibitor had been approved to treat several types of cancers. Nevertheless, underlying molecular mechanisms concerning how to regulate CDK6 expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Study in bladder cancer showed miR-934 down-regulated UBE2N protein expression by binding to 3ʹ-UTR of ubiquitin-conjugating enzyme 2N (UBE2N) mRNA, thereby inhibiting UBE2N-dependent degradation of CDK6 cyclin and promoting bladder cancer cell growth. 7 Recent studies have found that there are multiple microRNA expression differences in lung adenocarcinoma patients with EGFR exon 19 deletion compare with wild-type EGFR patients. The expression of miR-934 is up-regulated, especially in triple-negative invasive ductal carcinoma, but the mechanism remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study in bladder cancer showed miR-934 down-regulated UBE2N protein expression by binding to 3ʹ-UTR of ubiquitin-conjugating enzyme 2N (UBE2N) mRNA, thereby inhibiting UBE2N-dependent degradation of CDK6 cyclin and promoting bladder cancer cell growth. 7 Recent studies have found that there are multiple microRNA expression differences in lung adenocarcinoma patients with EGFR exon 19 deletion compare with wild-type EGFR patients. The expression of miR-934 is up-regulated, especially in triple-negative invasive ductal carcinoma, but the mechanism remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recent evidence also suggested that miR-934 targeting UBE2N could promote cell growth of bladder cancer by inhibiting CDK6 degradation. 7 The PROX1 encoding protein is a member of the homeobox transcription factor family and its function is mostly involved in lymphangiogenesis and angiogenesis. 8 Multiple studies have shown a close relationship between PROX1 and tumors, but due to the complexity of the interaction between pathways, PROX1 may play a completely paradoxical role in tumors.…”
Section: Introductionmentioning
confidence: 99%
“…For each analysis, the re y luciferase signal was normalized to the Renilla luciferase signal to eliminate the difference in transfection e ciency, as previously described (19).…”
Section: Dual-luciferase Reporter Assaymentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a group endogenous non-coding small RNAs, of ~22 nucleotides, which are widely reported in a variety of cancer types [7][8][9][10]. Several miRNAs, including miR-21, miR-23a, miR-410, miR-135, have shown potential to reverse the PI3K/AKT/mTOR pathway-induced inhibition of tumor growth, progression, and metastasis [5].…”
Section: Introductionmentioning
confidence: 99%